Research on Progressive Stabilization Filter System of Silt Foundation around Tube Well - Canhong Zhang; Wenang Hou; Enyue Ji; Zhanmin Yang; Baotian Wang (Advances in Civil Engineering)
To obtain the applicable filter layer range of the silt sand around the dewatering well of a ship lock renovation project in Nanjing, several existing classic filter layer criteria are analyzed, and the concept of a progressively stable filter system is put forward accordingly. The self-designed horizontal percolation filter is used to carry out the silt filter test, and the filter effect of these graded filter materials on the test silt filter is studied, and the mechanism of the progressively stable filter system is described. Tests show that when the ratio of the filter material to the characteristic particle size of the silt soil falls within the range of 4.3–7.7, the system maintains a stable percolation state. Through the particle tests of the base soil and the filter material after filtering, it is found that an effective filter system is that the filter layer induces soil’s self-filtration, and they work together. No matter what filter material criterion is used to design the filter, as long as the gradual and stable filtration mechanism is formed in the filtration process, stable filtration can be ensured. The research on the progressively stable filter system will help to determine the gradation range of the filter material more reasonably in the engineering design, reduce the failure probability of the filter layer, and provide a certain reference for the design of the filter layer in similar projects in the future.